Nanoparticulate materials : synthesis, characterization, and processing - Lu, Kathy (Wiley, 2013)
Serving as the only systematic and comprehensive treatment on the topic of nanoparticle-based materials, this book covers synthesis, characterization, assembly, shaping and sintering of all types of nanoparticles including metals, ceramics, and semiconductors. A single-authored work, it is suitable as a graduate-level text in nanomaterials courses